2019
DOI: 10.3390/ijerph16193715
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Local Heatwave Impact Assessment: A Case-Crossover Analysis of Hospital Emergency Department Presentations in Tasmania, Australia

Abstract: Heatwaves have been identified as a threat to human health, with this impact projected to rise in a warming climate. Gaps in local knowledge can potentially undermine appropriate policy and preparedness actions. Using a case-crossover methodology, we examined the impact of heatwave events on hospital emergency department (ED) presentations in the two most populous regions of Tasmania, Australia, from 2008–2016. Using conditional logistic regression, we analyzed the relationship between ED presentations and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 52 publications
(58 reference statements)
1
32
0
Order By: Relevance
“…Wang et al (2012) indicated a signi cant association between heat waves and diabetes mortality of the elderly aged over 75 years. No signi cant association between heat waves and diabetes was found in other four studies (Campbell et al 2019;Sherbakov et al 2018;Wilson et al 2013;Chen et al 2017).…”
Section: Overall Analysis Of Extreme Temperatures On Diabetesmentioning
confidence: 70%
See 1 more Smart Citation
“…Wang et al (2012) indicated a signi cant association between heat waves and diabetes mortality of the elderly aged over 75 years. No signi cant association between heat waves and diabetes was found in other four studies (Campbell et al 2019;Sherbakov et al 2018;Wilson et al 2013;Chen et al 2017).…”
Section: Overall Analysis Of Extreme Temperatures On Diabetesmentioning
confidence: 70%
“…Authors' contributions: XS made search strategy and wrote the article; LJ analyzed data, assessed risk of bias and wrote the article; DZ wrote the article; XW searched articles and assessed risk of bias; YM and YH selected studies and extracted data, XL and JT selected studies; YM and DZ wrote the protocol and registered at the PROSPERO; WH, AS and YF checked data and results of RoB assessment; YZ made some suggestions for improvement of this article. Basagaña et al 2011Campbell et al 2019Green et al 2010He et al 2019Kim et al 2015Liu et al 2018Méndez-Lázaro et al 2016Ostro et al 2010Xu et al 2019Stafoggia et al 2006Bai et al 2016Basu et al 2012Calkins et al 2016Gasparrini et al 2015Isaksen et al 2015Li et al 2017Li et al 2014bLi et al 2014aOgbomo et al 2016Åström et al 2015Pudpong and Hajat. 2011Seposo et al 2017Sherbakov et al 2018Chen et al 2017Vaneckova et al 2013Wang et al 2012Wang et al 2014Wilson et al 2013Winquist et al 2016Yang et al 2016Ma et al 2020 Overall analysis of extreme temperatures on diabetes Figure 3 Overall analysis of extreme temperatures on diabetes Figure 4 Overall analysis of extreme temperatures on diabetes Figure 5 Impact of heat exposures on diabetes mortality and morbidity Figure 7 Impact of heat exposures on diabetes mortality and morbidity…”
Section: Declarationsmentioning
confidence: 99%
“…Diagnosis coding used in previous literature examining heat-related illness was reviewed. Many of these studies utilised diagnostic blocks (code groups) rather than specific diagnoses to identify heat-related illness; however, this may result in the over-identification of conditions included as heat-related [ 3 , 4 , 9 , 10 , 11 , 12 , 32 , 33 , 34 ]. In order to increase the accuracy, ICD-10-AM codes from within previously identified diagnostic blocks [ 3 , 4 , 9 , 10 , 11 , 12 , 32 , 33 , 34 ] were rated independently for relevance by two investigators, both experienced clinicians.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of climate change, the global mean surface air temperature has shown a rising trend over the last 100 years [1], which has led to an increase in the frequency, intensity, and duration of extremes of heat since 1950 [2]. The most immediate and direct impact of rising temperature on human health is the increase in heat-related mortality and morbidity worldwide [3][4][5][6][7][8]. The 2003 heatwave in Europe resulted in around 15,000 heat-related deaths in France and around 70,000 deaths across Europe [9].…”
Section: Introductionmentioning
confidence: 99%